Durham Cathedral : the shrine of St. Cuthbert - Wood, David; Wood, David; Hodge, Jessica; Hodge, Jessica (Scala Arts and Heritage Publishers, Ltd, 2018)
Durham Cathedral is one of the great buildings of Europe. Set grandly on a rocky promontory next to Durham Castle, with the medieval city huddled below and the river sweeping around, the profile of this World Heritage Site is instantly recognisable. Started in 1093 and dedicated to Cuthbert, a Saxon saint, the cathedral was a pioneering building - which makes the 40 or so years it took to complete an astonishing achievement. The cathedral was a fitting symbol of the power of the Norman prince bishops, who were charged by the king to defend the realm from the constant threat of invasion. Perched on its rocky peninsula next to a great Norman fortification, the cathedral therefore spoke of human as well as divine power. This beautifully illustrated guide introduces the reader to the glories of Durham, and features the newly opened 'Open Treasure' exhibition